Korelasi Antara Penggunaan Power Point sebagai Media Pembelajaran dan Kemampuan Membaca Bahasa Inggris Siswa di Sekolah Menengah Kejuruan PGRI Pekanbaru Kelas XI - Irda Wati; Syahfutra, Wandi; Ardiya (EduTeach : Jurnal Edukasi dan Teknologi Pembelajaran, 2026)
This research aimed to investigate the correlation between the use of PowerPoint as a learning medium and students' reading comprehension in Grade XI at Vocational High School of PGRI Pekanbaru. A descriptive method was applied, using simple random sampling from a total population of 163 Grade XI students. Data collection involved questionnaires and reading tests, which were directly distributed to 32 students from two selected classes. The analysis results indicated no significant correlation between PowerPoint usage and students' reading comprehension, as shown by a significance value of 0.201 greater than 0.05 and a low correlation coefficient of 0.232, wich means the alternative hypothesis (H1) was rejected, while the null hypothesis (H0) was accepted. It can be concluded that PowerPoint has no relationship on students' reading comprehension. Further studies are recommended to investigate other factors that may influence students' reading comprehension.